Effects of aluminum phosphate sealant containing Al2O3 nanoparticles on the hardness and wear resistance of the Al2O3-TiO2 plasma sprayed coating - Ha, Pham Thi; Ly, Pham Thi; Tuan, Nguyen Van; Quan, Vo An; Quy, Le Thu (Vietnam Journal of Science and Technology, 2017)
In the present study, Al2O3-40% TiO2 composite coatings were fabricated on CT3 steel substrate by plasma spraying technique. The coatings were sealed with aluminum phosphate solution contained 5 wt.% Al2O3 nanoparticles and then heat treated at 400oC. The permeability of aluminum phosphate solution, phase composition, structure morphology, microhardness and wear resistance of the coating were studied. The study results phase composition of the coatings showed that the coatings were composed γ-Al2O3 and Al2TiO5 phase. The compounds AlPO4 and Al(PO3)3 were found in the coating sealed with aluminum phosphate. The presence of Al2O3 nanoparticles was increased the permeability of the aluminum phosphate solution into the coating. The coatings sealed  with aluminum phosphate contained Al2O3 nanoparticles have lower density, higher hardness and wear resistance higher than the coating sealed with aluminum phosphate uncontain Al2O3 nanoparticles and the unsealed coating.